Teaching the Translation of Arabic Legal Instruments: A Case Study of Iraqi Divorce Decrees - Rabea, Ahmed Falih (Advances in Social Sciences Research Journal, 2025)
This study is an attempt to shed light on teaching a court instrument, the divorce decree from Arabic into English taking into consideration all characteristics of legal discourse. It is a legal matter to approached carefully, namely with reference to legal terminology related to divorce documents. Divorce instruments are enriched with religious terminological aspects that require a thorough reading and understanding before commencing a translation process. Hence, this study is an endeavor to assist governmental and private translation departments and those interested in translation studies well understating how to come closer to a legal document such as a divorce decree having an eye to the main characteristics of legal discourse. Teaching translating a legal document is not merely a linguistic and structural matter which can be accomplished easily with zero cultural and religious mistakes. It is the case of translating cultural and religious norms from Arabic into English, which is a responsibility of a translator to fill in the gap between the source language (Arabic) and target language (English). The study has made plain that Arabic divorce documents are overflown with gaps that require a special attention of a legal translator while practicing his/her mission in translating such a divorce decree from Arabic into English, and has to wisely consider shutting off cultural and religious gaps as much as s/he can.